Analysis of the implementation of the waqf core principles on institutional financial performance waqf in Tanjungbalai, North Sumatera - Suhailah, Suhailah; Ramadhan, Muhammad; Marliyah, Marliyah (Goodwood Publishing, 2024)
Purpose: To analyze the effect of implementing a legal foundation, waqf supervision, good waqf governance, risk management, and Sharia governance on the financial performance of waqf institutions. Research Methodology: The research approach used in this study is a quantitative approach, with an associative type of quantitative research and a correlational quantitative research design that examines the relationship between two variables. The research data were analyzed using the SPSS statistical software. Results: The implementation of legal foundation, waqf supervision, good waqf governance, risk management, and Sharia governance have a positive and significant effect on the financial performance of the waqf institution in Tanjungbalai city. Then, based on the multiple linear regression equation, the variable that has the greatest influence on the financial performance of the waqf institution (Y) is good waqf governance (X3), followed by risk management (X4), Sharia governance (X5), legal foundation (X1), and Waqf supervision (X2). Limitations: As the scope of the search is not biased, it can focus more on avoiding errors in the objectives to be achieved. This study focuses on the implementation of the Waqf Core Principles for the financial performance of waqf institutions. Contributions: The results of this study may constitute a reference and provide information for future researchers who will discuss the development of waqf in North Sumatra. Thus, this research can be used as an input for recommendations to improve staffing institutions. The results of this study can be used as a basis for further study, revision, and development than previous research.